2010
DOI: 10.1080/10463283.2010.486942
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal behaviour and social perception in a hierarchy: The interpersonal power and behaviour model

Abstract: Power is a core dimension of social interactions and relationships. The present article addresses how power hierarchies form, how power is expressed and perceived via verbal and nonverbal behaviour during social interactions, and whether power of others can accurately be assessed. Taking into account the inherently relational and interactional nature of the power concept, an interpersonal power and behaviour model is presented. The model explicitly differentiates between different facets of power (status, posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 81 publications
1
29
0
1
Order By: Relevance
“…The interpersonal power and behavior model [23] also supports this finding and might be another explanation. This model claims that people with higher authority, power, or status are perceived as being more assertive, less pliable, and less persuadable.…”
Section: Discussion and Limitationssupporting
confidence: 66%
“…The interpersonal power and behavior model [23] also supports this finding and might be another explanation. This model claims that people with higher authority, power, or status are perceived as being more assertive, less pliable, and less persuadable.…”
Section: Discussion and Limitationssupporting
confidence: 66%
“…We also operationalized observers' verticality in two different ways: as an enduring personality trait that was measured in terms of personal sense of power, socioeconomic status (SES), or prenatal testosterone exposure (a correlate of dominance) in Studies 1 to 6; and as an ephemeral, transient state that was experimentally manipulated as a position of power, status, or dominance in Studies 7 to 12 (Ellyson & Dovidio, 1985;Hall et al, 2005;Hall, Schmid Mast, & Latu, 2014;Schmid Mast, 2010). A meta-analysis across these studies revealed that individuals were less likely to afford power to norm violators than to norm abiders, and that this effect was stronger among individuals with higher trait-but not state-verticality.…”
Section: Hypotheses and Overview Of Studiesmentioning
confidence: 99%
“…The first involves the power differential between the clergy and other church members. As research in social psychology reveals, differences in power can have a profound impact on the nature and frequency of social interaction (Mast, 2010). Second, because rank-and-file church members far outnumber pastors in a congregation, the opportunity to find a suitable source of informal support is greater in the pews than in the pulpit.…”
Section: Resultsmentioning
confidence: 99%